Determinants of Mobility Disability in Older Adults: Evidence from Population-Based Epidemiologic Studies - Inzitari, Marco (Premio Tesi di Dottorato, 2010)
Gait and mobility are cardinal to maintain autonomy and independency in daily life, also for older persons. Changes in these functions might be critical in the transition towards disability and loss of autonomy during the aging process. The aim of the present work, which collects three years of research conducted between Italy and the United States, was to assess some of the main risk factors for the progressive impairment of mobility and gait in older adults living in the community. According to our results, abnormalities in the nervous and cardiovascular systems, even subtle, are associated with a subsequent worsening of these functions. These data might help to better understand the progressive development of disability in the elderly, and in the future might also have practical implications for prevention.